2020
DOI: 10.1371/journal.pntd.0008796
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella identified in pigs in Kenya and Malawi reveals the potential for zoonotic transmission in emerging pork markets

Abstract: Salmonella is a major cause of foodborne disease globally. Pigs can carry and shed non-typhoidal Salmonella (NTS) asymptomatically, representing a significant reservoir for these pathogens. To investigate Salmonella carriage by African domestic pigs, faecal and mesenteric lymph node samples were taken at slaughter in Nairobi, Busia (Kenya) and Chikwawa (Malawi) between October 2016 and May 2017. Selective culture, antisera testing and whole genome sequencing were performed on samples from 647 pigs; the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Generally, animal farms are considered natural reservoirs of Salmonella, especially poultry and pigs (Li et al, 2013;Zhou et al, 2017;. Salmonella could colonize the digestive tract of animals and are excreted in feces and spread into the environment (Kagambèga et al, 2013;Bonardi, 2017;Jiang et al, 2019), then transmitted to humans via the food chain (Ed-Dra et al, 2018;Wang et al, 2019;Wilson et al, 2020;Liu et al, 2021). Therefore, several studies have reported the presence of Salmonella in foods of animal origin, especially meat products (Ed-Dra et al, 2017;Jiang et al, 2021;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, animal farms are considered natural reservoirs of Salmonella, especially poultry and pigs (Li et al, 2013;Zhou et al, 2017;. Salmonella could colonize the digestive tract of animals and are excreted in feces and spread into the environment (Kagambèga et al, 2013;Bonardi, 2017;Jiang et al, 2019), then transmitted to humans via the food chain (Ed-Dra et al, 2018;Wang et al, 2019;Wilson et al, 2020;Liu et al, 2021). Therefore, several studies have reported the presence of Salmonella in foods of animal origin, especially meat products (Ed-Dra et al, 2017;Jiang et al, 2021;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pork meat is considered the most frequently contaminated food and the major source of Salmonella infections in humans (Bonardi, 2017;Wilson et al, 2020). In fact, pig farms seem to be a suitable environment for the replication and the persistence of Salmonella (Lettini et al, 2016;Bonardi, 2017;Vico et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, a high prevalence of porcine and human cysticercosis has been reported (44)(45)(46), as well as non-typhoidal Salmonella isolates which were recovered from pig faecal samples (47). In neighbouring countries, trichinellosis, salmonellosis, and cysticercosis have been documented in pigs (48)(49)(50)(51)(52) and in humans (53,54).With the exception of the single modern abattoir, slaughter houses had intercrossing of clean and dirty operations, from killing through to carcass preparation. This is likely to lead to cross-contamination with pathogens such as Salmonella (55), especially as no running water was available inside the visited slaughterhouses, as has been reported elsewhere (49).…”
Section: Discussionmentioning
confidence: 99%
“…In neighbouring countries, trichinellosis, salmonellosis, and cysticercosis have been documented in pigs (48)(49)(50)(51)(52) and in humans (53,54).With the exception of the single modern abattoir, slaughter houses had intercrossing of clean and dirty operations, from killing through to carcass preparation. This is likely to lead to cross-contamination with pathogens such as Salmonella (55), especially as no running water was available inside the visited slaughterhouses, as has been reported elsewhere (49). Installing cold and hot water, as per international guidelines, can help to reduce occurrence of such contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is a Gram-negative zoonotic bacteria that is a leading cause of food-borne diseases in developed countries and causes bloodstream infections in infants and elderly in developing countries [ 33 ]. Salmonella are frequently asymptomatic in livestock, but has been highly associated with mild and severe diarrhea in piglets [ 34 , 35 ]. In pigs, Salmonella Typhimurium is by far the most isolated serotype in the EU and US, followed by Salmonella Derby and Salmonella Arizona.…”
Section: Introductionmentioning
confidence: 99%